'Clostridium massiliodielmoense', a new species isolated from the human gut microbiota. (September 2016) - Tidjani Alou, Maryam; Sokhna, Cheikh; Bittar, Fadi; Khelaifia, Saber; Fournier, Pierre-Edouard; Raoult, Didier
Abstract: Herein, we report the main characteristics of ' Clostridium massiliodielmoense ' strain mt26 (= CSUR P2255), representative of a new species isolated from the gastrointestinal tract of a healthy 28-month-old Senegalese boy.